Tunnel Digitalization Center - Beyond BIM in underground construction - Petschen, V.; Brandt, R.; Celebi, O.; Wyss, R.; Elkuch, N. (Expanding Underground - Knowledge and Passion to Make a Positive Impact on the World, 2023)
Digitalization opens the possibility of avoiding the waste of three very important assets. We can minimize the unnecessary loss of materials, time, and information by optimizing our use, presentation, and exchange of data. The more complex a construction is, the higher the number of participants in a project are, the bigger the infrastructure network of which a tunnel is part of, the better the digitalization shows its advantages. Digital continuity is the key for cross-phase and cross-divisional system solutions. With the help of 7 industry partners, under the coordination of the Swiss Center of Applied Technologies (SCAUT) the aim of the Tunnel Digitalization Center (TDC) is to showcase and develop new use-cases among very different stakeholders to innovate and demonstrate thirds the complex digital processes in a real environment. With this project, SCAUT aims to make an important contribution to the digitalization of the whole tunnelling industry. From BIM and electromechanical equipment to operation and digital services in maintenance, several possible applications of the digital twin: at the TDC solutions across the entire value chain and life cycle are demonstrated. It allows demonstration and simulation in a realistic environment. Innovative uses cases, like cloud solutions, BIM and IoT for tunnelling are part of it. In this paper the concept of the TDC is going to be presented, and the use cases shown there focusing on simulations, commissioning, operation, and maintenance. Even though an important development work has been done in the last years in the tunnelling industry, digitalization in tunnelling has still great further possibilities. A lot of communication among the different stakeholders is needed and a big amount of standardization processes must be done to profit of its full potential. The Tunnel Digitalization Center Project of Swiss Center of Applied Underground Technologies enables exactly this cross-industry communication among the different stakeholders, that is needed to push the digital transformation in tunnelling. With its demonstrations, it aims to play an educative and eye-opener role for new technologies. The Tunnel Digitalization Center was officially opened in October 2019 in the Hagerbach Test Gallery in Switzerland and is a project in permanent development since then. The Swiss Center of Applied Underground Technologies is a competency center for the use of the underground space.